Substitution Effects on the Bulk and Surface Properties of (Li,Ni)Mn2o4 - Gautier-Zamora, J; Gautier-Zamora, J; Alburquenque-Munoz, D; Alburquenque-Munoz, D; Casagrande-Denardin, J (Institute for Ionics, 2018)
Manganese oxides of spinel structure, LiMn2O4, Li1-xNixMn2O4 (0.25 ≤ x≤ 0.75), and NiMn2O4, were studied by EDS, XRD, SEM, magnetic (M-H, M-T), and XPS measurements. The samples were synthesized by an ultrasound-assisted sol-gel method. EDS analysis showed good agreement with the formulations of the oxides. XRD and Rietveld refinement of X-ray data indicate that all samples crystallize in the Fd3m space group characteristic of the cubic spinel structure. The a-cell parameter ranges from a = 8.2276 Å (x = 0) to a = 8.3980 Å (x = 1). SEM results showed particle agglomerates ranging in size from 2.3 μm (x = 0) down to 0.8 μm (x = 1). Hysteresis magnetization vs. applied field curves in the 5–300K range was recorded. ZFC-FC measurements indicate the presence of two magnetic paramagnetic-ferrimagnetic transitions. The experimental Curie constant was found to vary from 5 to 7.1 cm3 K mol−1 for the range of compositions studied (0 ≤ x ≤ 1). XPS studies of these oxides revealed the presence of Ni2+, Mn3+, and Mn4+. The experimental Ni/Mn atomic ratios obtained by XPS were in good agreement with the nominal values. A linear relationship of the average oxidation state of Mn with Ni content was observed. The oxide’s cation distributions as a function of Ni content from x = 0 Li+[Mn3+Mn4+]O4 to x = 1 Ni0.352+Mn0.653+[Ni0.652+Mn1.353+]O4 were proposed. © 2017, Springer-Verlag GmbH Germany.